Ação antifúngica de plantas medicinais e da própolis frente a leveduras do gênero Candida isoladas da cavidade bucal - Vargas Neto, Protásio (2004)
Candidosis is a current intraoral infection, resulting from temporary parasitism of Candida, mostly C. albicans. The use of phytotherapics for prevention and control of candidosis is not well stablished. The presence of Candida was determined in the oral cavity of 86 patients, 40 males and 46 females, aging from 18 to 82 yars, without clinical signs of candidosis by plating saliva samples on sabouraud dextrose. Candida was found in 38 (44,18%) individuals, 20 (23,25%) male and 18 (20,93%) female. From 38 samples, 18 were C. albicans, 13 C. tropicalis, 3 C. parapsilosis, 2 C. guilliermondii, 1 C. Krusei and 1 C. kerfyr. The sensitivity of these Candida isolates were evaluated throught three phytotherapics, Anacardium occidentale, Arctium lappa, Plantago major and the natural product propolis. The sensitivity of the yeasts was demonstrated in vitro, using a test of diffusion in agar and a test in tube to determine the number of yeasts killed by the phytotherapics and in vivo by the recovery of Candida from the oral cavity of rats treated with them and by the induction of candidosis in the rat´s tongue. As a comparison, tests with two types of commercial antifungal agents were performed. The results showed an effective action of propolis in both in vivo and in vitro tests. The most effetive phytotherapic was the cajueiro (Anacardium occidentale). Bardana (Arctium lappa) and tanchagem (Plantago major) showed less effetiveness without statistical significance.